Balancing Governance and Tradition: Navigating Political, Social, Economic, and Cultural Dynamics in Indonesian Village-Owned Enterprises - Fitriani, Desti; Shauki, Elvia R; Azim, Mohammad Istiaq (ASEAN Journal of Community Engagement, 2024)
This study examines the complex governance dynamics affecting Indonesian Badan Usaha Milik Desa (BUMDes) [village-owned enterprises], focusing on political, social, economic, and cultural pressures. Using a qualitative multi-case approach, including focus group discussions with 65 participants from West Java and West Nusa Tenggara, Indonesia, the study identified significant challenges: political interference, limited community engagement, economic dependence on government funds, and cultural norms that constrain BUMDes operations. Village elites frequently influence governance, limited capital access, and ingrained cultural values hinder transparency and open dialogue. To address these challenges, this study recommends a comprehensive approach comprising four key strategies: enhancing the institutional autonomy of BUMDes to reduce external interference, fostering that are transparent and inclusive government practices to ensure meaningful community participation, establishing sustainable funding models to secure financial independence, and integrating cultural adaptability into governance frameworks. Together, these strategies aim to build a resilient and inclusive governance structure for BUMDes, enabling them to fulfill their role in future village empowerment and economic development effectively.